Pengembangan Perangkat Pembelajaran Model Problem Based Learning untuk Meningkatkan Kreativitas dan Hasil Belajar Fisika Peserta Didik - Setiati, Nunung; Gunawan, Gunawan; Doyan, Aris; Sutrio, Sutrio (Indonesian Journal of STEM Education, 2020)
This study aims to develop the valid, practical, and effective teaching by using problem based learning model. This method of this study is R&D (Research adn Development). This study involves research and divelopment using 4D (Define, Design, Develop, and Development) learning model. This study produces learning instrumen such as syllabus, lesson plan, students worksheet, learning video, and test instruments. Learning devices are validated by three validators of mataram university physics education and three validators by high school teachers. Limited trial subjects are students of class X MIPA 1 SMAN 6 Mataram. The result of this study shows that 1) learning student by using problem based learning model such as syllabus, lesson plan, students worksheet, learning video, and test instruments includes in valid category, 2) students and teacher’s response to learning student by using problem based learning model includes in good category, 3) learning student by using problem based learning model is effective to use in online learning. From this result of the study, it can be concluded that the developed learning instrument is valid, practical, and effective. Keywords: PBL; Development; Learning Instrument, Creativity, Learning Results